Konsistensi Representasi Kecantikan Inklusif Iklan Instagram @cantikcitra Periode 2024-2025: Analisis Semiotika Iklan - Almas Nurhidayah Ningsih; Adi Nugroho (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzed the consistency of inclusive beauty representation in two Instagram ad campaigns @cantikcitra. The 2024 campaign echoes the 'Beautiful Hands'. Meanwhile, the 2025 campaign echoes 'Skin Serum'. This study uses Roland Barthes' semiotic analysis. The research aims to reveal how visual and verbal signs form the meaning of inclusivity and assess the continuity of communication strategies across time. The results show that both campaigns maintain a soft aesthetic, warm colors, and emphasize authenticity. However, in the period 2024 to 2025 there will be a shift in meaning. The 2024 advertising campaign constructs inclusivity through the representation of women's social roles. While the 2025 ad campaign emphasizes personal experience, self-acceptance and emotional closeness. The level of myth is generated that in two periods builds the narrative that beauty no longer depends on physical standards. But in the comfort of being yourself. Although aesthetically consistent, the representation of diversity is still within the boundaries of the mainstream, inclusivity. Based on these results, it is confirmed that the importance of ethical commitment and participatory strategies for brands. Of course, it aims to be a solid fortress so that the value of inclusivity does not stop at visual symbols. However, it becomes a substantive and sustainable communication practice